1998
DOI: 10.1007/s002469900276
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Evidence for a Ductal Tissue Sling Causing Discrete Coarctation of the Aorta in the Neonate: Case Report

Abstract: A neonate presented to our institution with the physical findings of coarctation of the aorta. After starting prostaglandin E1 the signs and symptoms resolved despite persistent closure of the ductus arteriosus. We present echocardiographic evidence to support the contention that a ductal tissue sling contributes to the formation of juxtaductal coarctation of the aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…10 The exact pathophysiological mechanisms that lead to the development of CoA are still poorly understood, despite the first such theories being proposed over 180 years ago. [11][12][13][14][15][16][17] The so-called branching theory, proposed by Hutchins 14 in 1971, postulates that reduced or reversed flow at the isthmus leads to the distal arch becoming a functional branch of the DA (Figure 1). This theory is based on the observation, from surgically resected specimens, that the posterior shelf-the ridge of infolded tissue associated with isthmal obstruction following DA closure-is histologically identical to the arterial infolding seen in other major aortic branches.…”
mentioning
confidence: 99%
“…10 The exact pathophysiological mechanisms that lead to the development of CoA are still poorly understood, despite the first such theories being proposed over 180 years ago. [11][12][13][14][15][16][17] The so-called branching theory, proposed by Hutchins 14 in 1971, postulates that reduced or reversed flow at the isthmus leads to the distal arch becoming a functional branch of the DA (Figure 1). This theory is based on the observation, from surgically resected specimens, that the posterior shelf-the ridge of infolded tissue associated with isthmal obstruction following DA closure-is histologically identical to the arterial infolding seen in other major aortic branches.…”
mentioning
confidence: 99%
“…The patient was surgically repaired via subclavian flap aortoplasty. 9 In another unique case of coarctation in a patient with a persistent fifth aortic arch, prostaglandin infusion relieved the obstruction, with an improvement in femoral pulses, and echocardiographic narrowing without opening the ductus. 10 It has also been reported that in a premature baby with coarctation, whose ductus had been previously ligated, prostaglandin infusion successfully ameliorated symptoms of heart failure.…”
Section: Discussionmentioning
confidence: 98%
“…Callahan et al reported a nine-day-old neonate with significant coarctation in the juxtaductal region without a patent ductus. 9 Prostaglandin infusion resulted in clinical and echocardiographic resolution and its discontinuation resulted in recurrence of signs of coarctation. The patient was surgically repaired via subclavian flap aortoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Liberman reported three term neonates with coarctation of the aorta and a closed ductus who were treated with prostaglandin E 1 infusions; prostaglandin therapy was only used for short periods since each infant underwent early corrective surgery 1. Callahan et al also reported the short-term use of prostaglandin E 1 in a near-term baby in whom a trial of cessation of prostaglandin therapy resulted in a worsening of the aortic constriction 4…”
Section: Discussionmentioning
confidence: 99%